A 16S rDNA sequencing-based analysis of airway microecology in patients with an acute exacerbation of chronic obstructive pulmonary disease: A cross-sectional study in Inner Mongolia, China - Zhu, Shu-fen; Wu, Xin-xin; Guo, Yan; Li, Peng-fei; Wang, Jing-ran; Liu, Miao; Luo, Cheng-wen; Yuan, Xiang-zhen; Li, Shao-wei (Frontiers in Medicine, 2022)
Aim To study the microecological characteristics of the airway and similarities and differences between healthy people and patients with the acute exacerbation of chronic obstructive pulmonary disease (AECOPD) in Inner Mongolia, and analyze the correlation between the characteristics of the airway microecological structure and clinical indicators of AECOPD patients. Methods Sputum samples from 36 healthy volunteers and 34 patients with AECOPD were detected by 16S rDNA high-throughput sequencing, and the airway microecological characteristics of healthy people and AECOPD patients were revealed by an alpha diversity analysis, beta diversity analysis and LefSe difference analysis. Results There were differences in the airway microecological structure between healthy people and AECOPD patients in Inner Mongolia. The airway microbiota composition of AECOPD patients showed an increase in the abundance of common pathogens and a decrease in the abundance of commensal bacteria, and the airway microbial diversity in AECOPD patients was lower than that in healthy people. Long-term use of inhaled glucocorticoid + long-acting β2 agonist mixture (ICS+LABA), procalcitonin (PCT), blood monocyte count (MONO), hemoglobin (HGB), D-dimer (D-D) and body temperature were negatively correlated with the alpha diversity of the airway micro-ecosystem. Conclusion The airway microecological composition of the AECOPD population in Inner Mongolia was different from that of the healthy population, and the airway microecological diversity was lower than that of the healthy population. The long-term use of ICS+LABA preparation by patients with AECOPD leads to lower alpha diversity. Alpha diversity was negatively correlated with inflammatory markers (PCT, MONO, D-dimer, body temperature) and HGB in AECOPD patients.